Research Progress of Fault Diagnosis Technology of Gear Transmission System - Wang Jingyue; Wang Haotian; Guo Lixin (Jixie chuandong)
The gear transmission system is the most widely used motion or power transmission device,such as vehicles,machinery,aviation,aerospace,metallurgy,electric power,coal,petrochemical,nuclear energy and many other key mechanical equipment in the industry. The fault of gear transmission system will cause mechanical equipment failure. If the diagnosis can be carried out in advance,it is effective to avoid the occurrence of accidents,eliminate the continued damage,save a lot of maintenance costs. In view of the research results in the field of fault diagnosis technology of the gear transmission system,focusing on the research status of the fault feature extraction and mode recognition method,and the problems to be further study is given.